Applying economic theories to build land price model and develop land bank: A case study of Vinh Long, Viet Nam - Bao, Le Tran; Phuong, Nguyen Ngoc Duy (Edelweiss Applied Science and Technology, 2024)
The paper explores the relationships between land price and land bank in the well – known philosophy of the urban economic theory and the bid rent theory. Based on those, the article aims to determine the impact of factors on land prices and propose some recommendations for creating a land bank to implement investment projects in Vinh Long province. Secondary data was collected from agencies and functional units in Vinh Long province. Primary data was collected through a survey of 144 knowledgeable people related to state management of land, land prices, and land bank creation. The data were analyzed through Cronbach’s Alpha coefficient, factor analysis, and testing of the SEM linear structural model using Smart PLS software. There are 36 measured factors belonging to 7 groups of factors included in the regression model, of which five groups of factors impact land prices and are intermediate factors affecting the creation of land banks. When determining land prices, it is necessary to pay attention to the level of impact of groups of factors on residential land prices, such as supply and demand, land plot location, urbanization, and so on, to determine appropriate land prices in each situation. The stage of the urbanization process ensures harmony between the state’s interests, land users, and other subjects related to creating a land bank in Vinh Long province.